Emergent Noncentrosymmetry and Piezoelectricity Driven by Oxygen Octahedral Rotations in n = 2 Dion–Jacobson Phase Layer Perovskites. (5th February 2016) - Strayer, Megan E.; Gupta, Arnab Sen; Akamatsu, Hirofumi; Lei, Shiming; Benedek, Nicole A.; Gopalan, Venkatraman; Mallouk, Thomas E.
Abstract : The loss of centrosymmetry via oxygen octahedral rotations is demonstrated in the n = 2 Dion–Jacobson family of layered oxide perovskites, A′LaB2 O7 (A′ = Rb, Cs; B = Nb, Ta). Ab initio density functional theory calculations predict that all four materials should adopt polar space groups, in contrast to the results of previous experimental studies that have assigned these materials to the centrosymmetric P4/ mmm space group. Optical second harmonic generation experiments confirm the presence of a noncentrosymmetric phase at ambient temperature. Piezoresponse force microscopy experiments also show that this phase is piezoelectric. To elucidate the symmetry‐breaking and assign the appropriate space groups, the crystal structure of CsLaNb2 O7 is refined as a function of temperature from synchrotron X‐ray diffraction data. Above 550 K, CsLaNb2 O7 adopts the previously determined centrosymmetric P4/ mmm space group. Between 550 and 350 K, the symmetry is lowered to the noncentrosymmetric space group A mm 2. Below 350 K, additional symmetry lowering is observed as peak splitting, but the space group cannot be unambiguously identified. Abstract : Oxygen octahedral rotations lower the symmetry in the Dion–Jacobson family of layered oxide perovskites, A′LaB2 O7 (A′ = Rb, Cs; B = Nb, Ta). Loss of centrosymmetry below a critical temperature is evidenced by optical second harmonic generation and by the appearance of superlattice reflections in X‐ray diffraction patterns.